Juridical Review of Dissenting Opinion of Decision No.90/PUU-XXI/2023 Related to The Argument Of Open Legal Policy and The Code of Ethics Of MK Judges - Kurnia Ali Syarif (Universitas Negeri Makassar, 2024)
The Constitutional Court (MK) Decision No. 90/PUU-XXI/2023 has attracted widespread attention regarding the dissenting opinion arguments put forward by a number of judges regarding the application of the Open Legal Policy (OLP) principle and the Code of Ethics of MK Judges. In this juridical review, we explore the various arguments contained in the dissenting opinion of Decision No. 90/PUU-XXI/2023, particularly those related to legal considerations related to OLP and the moral obligations of judges in interpreting and applying the law. This abstract aims to provide a comprehensive overview of the dynamics of legal interpretation and conflicting arguments in the context of this controversial Constitutional Court decision. By analyzing the arguments put forward in the dissenting opinion, we highlight the complexity of the legal and ethical issues involved, as well as the implications for the legitimacy and authority of the constitutional court. Through this review, it is hoped that a deeper insight into how the Constitutional Court dealt with the conflict between OLP and judges' code of ethics in the context of its decision-making can be found, as well as the implications of this decision for the future of constitutional justice in our country.